The Influence of Celebrity Endorsers and Online Promotion on Purchasing Decision through Brand ImageInfluence Of Celebrity Endorsers And Online Promotion On Purchasing Decision Through Brand Image - Misbahul Anwar; Sutrisno Wibowo; Andrian; Intan Nur Setiyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the influence of celebrity endorsers and online promotions on purchasing decisions through brand image as a mediating variable on SKINTIFIC and Tasya Farasya products as celebrity endorsers. This type of research is quantitative research using primary data. This study uses Structural Equation Modeling (SEM) AMOS 21 analysis tool. Based on the results of the study, it showed that celebrity endorsers had a positive and significant effect on purchasing decisions, online promotion had a positive and significant effect on purchasing decisions, celebrity endorsers had a positive and significant effect on brand image, online promotion had a positive and significant effect on brand image, brand image had a positive effect and significantly to purchasing decisions, brand image is able to mediate the influence of celebrity endorsers on purchasing decisions, and brand image is able to mediate online promotions on purchasing decisions.